1996
DOI: 10.1180/minmag.1996.060.401.14
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatian coffinite with rare earth elements and Ce-rich françoisite-(Nd) from sandstone beneath a natural fission reactor at Bangombé, Gabon

Abstract: SPONTANEOUS fission reactions occurred in several uranium deposits in SE Gabon approximately two billion years ago. The reactor zones, between 10 to 50 cm thick, are found in Proterozoic sandstones and consist of high-grade uranium ore mantled by illite and/or chlorite (Gauthier-Lafaye et al., 1989). During a mineralogical study of sandstones (quartz arenites) underlying a natural fission reactor at Bangomb6 (20 km south of the Oklo uranium deposit), we have found several grains of a uranous silicate, coffinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 6 publications
0
38
1
Order By: Relevance
“…A previous study of REE isotopes of the Bangombé reactor showed that the elemental abundances of non-fissiogenic REE in the Bangombé RZ are very low (⌺REE Ͻ 500 ppm) despite its high U concentration (29.5-45.0 wt.%; Hidaka and Gauthier-Lafaye, 2000). In addition, REE patterns (Hidaka and Gauthier-Lafaye, 2000) and mineralogical observation (Janeczek and Ewing, 1996b;Jensen and Ewing, 1998) suggest that uraninite in the Bangombé RZ has been partially dissolved and affected by supergene alteration. In particular, Stille et al (2003) described the enrichment of LREE in groundwater that passes through the Bangombé uranium deposit.…”
Section: U and Ree Differentiationmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous study of REE isotopes of the Bangombé reactor showed that the elemental abundances of non-fissiogenic REE in the Bangombé RZ are very low (⌺REE Ͻ 500 ppm) despite its high U concentration (29.5-45.0 wt.%; Hidaka and Gauthier-Lafaye, 2000). In addition, REE patterns (Hidaka and Gauthier-Lafaye, 2000) and mineralogical observation (Janeczek and Ewing, 1996b;Jensen and Ewing, 1998) suggest that uraninite in the Bangombé RZ has been partially dissolved and affected by supergene alteration. In particular, Stille et al (2003) described the enrichment of LREE in groundwater that passes through the Bangombé uranium deposit.…”
Section: U and Ree Differentiationmentioning
confidence: 91%
“…Among the four thin sections, the samples 1225 and 1290 are the same samples in which REE-bearing françoisite, (REE)(UO 2 ) 3 O(OH)(PO 4 )6H 2 O, and Uenriched goethite, FeOOH were previously discovered, respectively (Janeczek and Ewing, 1996b;Janeczek, 1999). Although mineral observation and chemical analysis of major elements of françoisite and goethite were previously carried out by Janeczek and Ewing (1996b), the isotopic measurements were not performed. Besides the françoisite and goethite, in this study we found several phosphorus coffinite grains in BAX03.1225 and 1240, and uraninite grains in 1215 and 1290 that were subjected for isotopic analyses.…”
Section: Samplesmentioning
confidence: 98%
“…Stable U(IV) minerals, which could form as secondary phases, would impart lower uranium solubility to such systems. Thus, knowledge of coffinite thermodynamics is needed to constrain the solubility of U(IV) in natural environments and would be useful in repository assessment.In natural uranium deposits such as Oklo (Gabon) (4,7,11,12,14,17,18) and Cigar Lake (Canada) (5, 13, 15), coffinite has been suggested to coexist with uraninite, based on electron probe microanalysis (EPMA) (4,5,7,11,13,17,19,20) and transmission electron microscopy (TEM) (8, 15). However, it is not clear whether such apparent replacement of uraninite by a coffinite-like phase is a direct solid-state process or occurs mediated by dissolution and reprecipitation.…”
mentioning
confidence: 99%
“…In natural uranium deposits such as Oklo (Gabon) (4,7,11,12,14,17,18) and Cigar Lake (Canada) (5,13,15), coffinite has been suggested to coexist with uraninite, based on electron probe microanalysis (EPMA) (4,5,7,11,13,17,19,20) and transmission electron microscopy (TEM) (8,15). However, it is not clear whether such apparent replacement of uraninite by a coffinite-like phase is a direct solid-state process or occurs mediated by dissolution and reprecipitation.…”
mentioning
confidence: 99%
“…In recent years "natural analogues" for both the repository environment (e.g., the Oklo natural reactors) and nuclear waste form behavior (e.g., corrosion and alteration of uraninite, UO 2+x ) have been cited as a fundamental means of achieving confirmation of long-term extrapolations (Ewing and Jercinovic, 1987;Ewing, 1991Ewing, , 1992Ewing, , 1993aEwing, , 1993bEwing, , 1999b. In particular, considerable effort has already been made to establish that uraninite, UO 2+x , with its impurities, is a good structural and chemical analogue for the analysis of the long-term behavior of the UO 2 in SNF (Fayek et al, 1997a;Janeczek and Ewing, 1991aJaneczek et al, 1993Janeczek et al, , 1996aJaneczek et al, , 1996bMurphy, 1993;Pearcy et al, 1994). …”
Section: Introductionmentioning
confidence: 99%